The influence of chief audit executive’s leadership style, internal audit independence and management support on internal audit effectiveness: Evidence from China / Liu Ruiling - Liu , Ruiling (2023)
The purpose of this study is to discuss the Chinese auditors' views on the effectiveness of internal audit and to examine the leadership style of the chief audit officer, the independence of internal audit and the relationship between management support for internal audit and the effectiveness of the internal audit. In this study, the internal auditors of large Chinese organisations were selected as samples. Only those listed companies in China with internal audit function (IAF) in-house were concerned with the sampling framework. The study method used in this study was PLS-SEM analysis, with a total sample of 273 respondents. The results show that leadership style and independence of internal audit and the relationship between management support internal audit effectiveness have a positive and significant impact. This study provides evidence that CAE leadership style significantly affects the identified attributes of perceived IA effectiveness and demonstrates that the independence of internal audit and the degree of management support for the internal audit function contribute to the effectiveness of the internal audit function in Chinese listed companies. Theoretically, this study can benefit from and contribute to the research on the effectiveness of internal audit because it expands the existing literature on the factors affecting the effectiveness of internal audit in the Chinese environment. This study can provide helpful information for policymakers, governments, and professional accounting institutions in developing countries with similar economic, political, and cultural backgrounds and establish policies and frameworks related to audit effectiveness to ensure adequate supervision of capital markets.